The position of cooperatives in the new social economy = Miejsce spółdzielczości we współczesnej ekonomii społecznej - Czternasty, Waldemar (Zielona Góra: Faculty of Economics and Management Press)
A dynamic development of market economy, broadly understood globalisation, the welfare state crisis in Western Europe etc. cause the intensification and creation of new aspects of poverty, marginalisation and social exclusion. The capabilities to solve the increasing social issues must be connected with the idea of social economy which assumes, among other things, facilitating the employment participation, access and use of any resources, laws, products and services. The opportunities of implementing those actions are linked to functioning of a specific group of entities which perform, along with the economic activity, also a social mission.
Keywords: ekonomia komercyjna; społeczność; ekonomia społeczna; misja społeczna państwa; podmioty ekonomii społecznej; commercial economy; cooperative movement; social economy; social mission of the state; social economy entities